Expanding Downward: Innovation, Diffusion, and State Policy Adoptions of Universal Preschool - F. Chris Curran (Arizona State University, 2015)
Framed within the theoretical framework of policy innovation and diffusion, this study explores both interstate (diffusion) and intrastate predictors of adoption of state universal preschool policies. Event history analysis methodology is applied to a state level dataset drawn from the Census, the NCES Common Core, the Book of the States, and other sources. Significant predictors of policy adoption include greater Democratic control of the state legislature and the prolonged presence of a targeted preschool program. Regional proximity is not found to be a significant predictor of policy adoption. Implications for policy and practice are discussed.